Mitigasi Risiko Penggunaan PGPR pada Usahatani Bawang Merah di Kabupaten Nganjuk Indonesia - Irzaq Galuh; Fitri Krismiratsih; Suwinda Fibriani; Dwi Putri Sunaryanti; Dini Nafisatul Mutmainah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The adoption of plant growth-promoting rhizobacteria (PGPR) in Indonesia remains limited, despite their potential to improve crop productivity and reduce dependence on synthetic inputs in intensive shallot production systems. This study aims to identify and prioritize the key risk sources that impede PGPR adoption and to formulate institution-oriented mitigation strategies. The research was conducted in Nganjuk Regency, East Java, using the House of Risk (HOR) framework to characterize risk events, link them to their causal agents, and derive a hierarchy of preventive actions based on their Aggregate Risk Potential. The results reveal that the most influential risks arise from institutional and behavioral dimensions rather than from the technical aspects of PGPR application. Weak institutional support, limited technical assistance during the transition phase, and inadequate dissemination of scientific information were identified as the primary factors shaping farmers’ perceptions of uncertainty and adoption decisions. Technical considerations related to product formulation or field performance exerted comparatively lower influence on the overall risk structure. Based on the prioritization outcomes, three mitigation directions are highlighted: strengthening cross-institutional coordination to ensure coherent support mechanisms, enhancing the capacity and engagement of extension officers to facilitate knowledge transfer, and establishing participatory learning platforms that allow farmers to observe and validate PGPR performance under local conditions. These measures are expected to reduce perceived uncertainty and create enabling conditions for more consistent uptake of biological inputs. In summary, this study identifies the primary risk sources that constrain PGPR adoption and provides a set of targeted, institution-based mitigation strategies derived from a structured risk analysis. The findings provide an evidence-based foundation for strengthening institutional support systems and identify avenues for future research on communication models and institutional interventions to enhance the diffusion of biofertilizers in smallholder farming systems.